New fossil species of Nymphidae (Neuroptera) from the Eocene of North America and Europe - Archibald, S. Bruce; Makarkin, Vladimir N.; Ansorge, Jörg (Zootaxa, 2009)
Two new fossil species of Nymphidae (Neuroptera) are described: Nymphes georgei sp. nov. from the Early Eocene locality at Republic, Washington, U.S.A., and Pronymphes hoffeinsorum sp. nov. from Late Eocene Baltic amber. The assignment of the new Republic species to Nymphes Leach maintains some doubt. This is the first fossil record of the genus (or one very closely related), today restricted to the Australian region, and its biogeographical implications are briefly discussed. The genus Pronymphes Krüger is considered to be valid and a diagnosis is provided, as is an amended diagnosis for the wings of Nymphes.